Effect of different sodium chloride (NaCl) concentration on corrosion of coated steel - Mohd Firdaus, Ibrahim (2013)
One of the ways to prevent the corrosion from occurs is coating or painting. Paint is used as protector to the materials such as mild steel that prevent the corrosion to occur. Besides that, the corrosion rate in different concentration of Sodium Chloride (NaCl) solution is different. This study is carried on the 5 sample of mild steel as specimen that immersed in different concentration of NaCl that is 0% of NaCl, 1.5% of NaCl, 2.5% of NaCl, 3.5% of NaCl and 4.5% of NaCl. This study is carried 6 days and the result is obtained by photo snapping at second day (2nd day), fourth day (4th day) and sixth day (6th day) continuously. The paint quality is analyzing from width of corrosion, peeling, wear off and changes in colour. After that, to obtain the corrosion rate, the mass loss experiment was carried out. The purpose of this study is to study the corrosion on coated steel in different concentration of NaCl solutions. Besides that, this study also to investigate the performance of protective coating on steel in different concentration of NaCl solutions. At the end of the experiment, we can conclude that the corrosion rate is increase when the concentration of NaCl solution is also increase. Other than that, the performance of the protective coating especially paint on steel is different when it immersed in the different concentration of NaCl that is the quality of paint in 4.5% of NaCl solution is most fast to decrease.